Thermosensitive hydrogel loaded with concentrated growth factors promote bone repair in segmental bone defects - Zhang, Yuxin; Wang, Tianchang; Zhang, Dahe; Li, Jiayi; Yue, Xiaokun; Kong, Weiqing; Gu, Xiaoding; Jiao, Zixian; Yang, Chi (Frontiers in Bioengineering and Biotechnology, 2022)
Treating critical-size bone defects beyond the body's self-healing capacity is a challenging clinical task. In this study, we investigate the effect of concentrate growth factors (CGFs) loaded Poloxamer 407 hydrogel on the viability and osteogenic differentiation potential of bone marrow mesenchymal stem cells (BMSCs) and reconstruction of critical-size bone defects. In vitro, this CGFs-loaded thermosensitive hydrogel can significantly promote proliferation, maintain cell viability, and induce osteogenic differentiation of BMSCs by up-regulating the mineralization and alkaline phosphatase (ALP) activity, as well as gene markers, including runt-related transcription factor-2 (Runx-2), type I collagen (Col-1), osteocalcin (OCN), as well as osteopontin (OPN). In vivo, Micro-CT radiography analysis and histological detection demonstrated that the CGFs-loaded hydrogel significantly induced bone healing and reconstructed the medullary cavity structure in critical-size bone defect models. In conclusion, this strategy of transplantation of CGFs-loaded hydrogel promoted bone regeneration and prevented bone nonunion, so as to provide basis for clinical treatment for repairing critical-size bone defects.